2016
DOI: 10.13109/zptm.2016.62.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability during Inpatient Psychosomatic Treatment - A Naturalistic Observational Study

Abstract: Reductions of psychological distress may not be reflected by improved autonomic function. Studies on interventions that may improve both psychological distress and autonomic dysfunction are desirable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Both the results indicate reduced parasympathetic activity in somatoform disorder patients. In a different study, Viehof Z. et al (2016) found reduced heart rate variability among somatoform disorder patients 16 . Heart rate variability means beat to beat variation in length of time and it is a measure of parasympathetic activity.…”
Section: Study Variables Of Autonomic Functionmentioning
confidence: 94%
“…Both the results indicate reduced parasympathetic activity in somatoform disorder patients. In a different study, Viehof Z. et al (2016) found reduced heart rate variability among somatoform disorder patients 16 . Heart rate variability means beat to beat variation in length of time and it is a measure of parasympathetic activity.…”
Section: Study Variables Of Autonomic Functionmentioning
confidence: 94%
“…Regarding the clinical characteristics of the samples, anxiety conditions with anxiety disorder as the primary condition were most prevalent (Blanck et al, 2019;Garakani et al, 2009;Stratford et al, 2014;Sullivan et al, 2004). Other disorders of lower prevalence in the literature were anxiety or other mood disorders (Wheeler et al, 2014), posttraumatic stress disorder (PTSD; Doukas et al, 2014) and PTSD comorbid with substance abuse disorder (Soder et al, 2019), separation anxiety disorder (Milrod et al, 2016), depressive disorder (Blanck et al, 2019;Caldwell & Steffen, 2018;Carney et al, 2000;Kim et al, 2009;Neyer et al, 2021;Zimmermann Viehoff et al, 2016), bipolar disorder (Howells et al, 2014), somatoform disorders (Angelovski et al, 2016;ZimmermannViehoff et al, 2016), adjustment disorder (ZimmermannViehoff et al, 2016, low trait positive affect (Lü et al, 2013), and mental or psychosomatic symptoms in general (Balint et al, 2022).…”
Section: Overview Of Treatments and Sample Characteristicsmentioning
confidence: 99%
“…The most prevalent clinical orientation was cognitive behavioral therapy (CBT) and CBT variants, e.g., for substance abuse disorder (Blanck et al, 2019;Caldwell & Steffen, 2018;Soder et al, 2019), in forest environments (Kim et al, 2009), combined with biofeedback (Angelovski et al, 2016), and mindfulnessbased (Howells et al, 2013). Other orientations were a diversity of psychodynamic therapies (Angelovski et al, 2016;Milrod et al, 2016;Stratford et al, 2014;ZimmermannViehoff et al, 2016), group positive psychotherapy (Lü et al, 2013), and eclectic or miscellaneous approaches (Balint et al, 2022;Doukas et al, 2014). A total of 960 participants (excluding psychotherapists) of which 743 received psychotherapy were included in the review.…”
Section: Overview Of Treatments and Sample Characteristicsmentioning
confidence: 99%
“…Altered HRV with increased low-frequency and reduced high-frequency power has been found in various pain-related disorders [32,33], indicating an increased sympathetic and reduced vagal tone [34]. Research also suggests sympathetic over-activation and reduced HRV in psychosomatic inpatients [35] and patients with somatic symptom disorder, respectively [33].…”
Section: Introductionmentioning
confidence: 99%